Newfoundland Poetry as "Ethnographic Salvage": Time, Place, and Voice in the Poetry of Michael Crummey and Mary Dalton - Chafe, Paul (Studies in Canadian Literature, 2007)
Michael Crummey's Hard Light (1999) and Mary Dalton's Merrybegot (2003) are two poetry collections that participate in a rare and vital form of what James Clifford has derisively called "ethnographic salvage." Through their replication of the languages and lives of Newfoundlanders, Crummey and Dalton avoid the tropes and clichés of Newfoundland identity, which reinscribe what Graham Huggan calls the "anthropological exotic," and instead capture the "performative nature" of individuals living within this culture. In a province that is steadily losing its longstanding cultural connection to the fisheries, the poems of Crummey and Dalton mark the preservation of actions and expressions in a way sensitive to what Homi K. Bhabha calls cultural hybridity.